Production of Striped Catfish (Pangasius sutchi) In Intensive Cultivation Reviewed From Abudance Of Algae At The Pond Red-Yellow Podzolic Soil In Different Ages - Sri Purwahyuningsih; Syafriadiman '; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The aim of the study is to determine the striped catfish production reviewed of the abundance of algae of land owned by an PMK different age as a container maintenance. The method used in this study is the experimental method using a completely randomized design (CRD) using 1 factor, 4 levels of treatment and 3 repetitions, with treatment are: P1 (intensive pond of catfish aquaculture age 0-5 years), P2 (intensive pond of catfish aquaculture age 6-10 years), P3 (intensive pond of catfish aquaculture age 11-15 years) and P4 (intensive pond of catfish aquaculture age16-20 years). The result showed that 27 species were found and consisted of Xanthophyta (5 species), Euglenophyta (1 species), Cyanophyta (10 species), Bacillariophyta (4 species) and Chlorophyta (7 species). Algae abundance of the best in the P3 (pond aged 11-15 years) is 41, 435 Ind / cm2. For the production of striped catfish in P4 (pond aged 16-20 years) is the best treatment which has a high production rate of 6.4 kg / m2, with SR of 66.5% with FCR of 1.9%.Keyword : Production of striped catfish (Pangasius sutchi), Algae, Red-Yellow Podzolic Soil , Intensive